Subsolidus solution and electrical properties of Sr-substituted bismuth magnesium niobate pyrochlores - Mat Dasin, Nurul Aidayu; Tan, Kar Ban; Khaw, Chwin Chieh; Zainal, Zulkarnain; Chen, Soo Kien (Elsevier, 2017)
Here we investigated the structural and dielectric properties of (Bi3.36Mg0.64-xSrx)(Mg1.28Nb2.72)O13.76 (0≤ x≤0.5) subsolidus solution. Sr-substituted bismuth magnesium niobate (BMSN) pyrochlores were prepared by solid-state reaction at 1025 °C over 1–2 days. X-ray diffraction (XRD) analysis confirmed that the BMSN pyrochlores crystallise in cubic symmetry, space group Fd3m with lattice parameters in the range 10.5968 (4)-10.5671 (17) Å. The surface morphologies of these samples, as confirmed by Scanning Electron Microscopy (SEM), were composed of irregular shaped grains. Both Scherrer and Williamson-Hall methods revealed that the crystallite sizes were in the range 46–75 nm. No thermal event was discernible over the temperature range 30–1000 °C, thus confirming the thermal stability of these materials. On the other hand, Arrhenius conductivity plots showed the BMSN pyrochlores to be highly insulating with activation energies of ~1.20–1.49 eV. At ~30 °C and 1 MHz, BMSN pyrochlores exhibited moderate high bulk dielectric constants, ɛ’, 90–186 and low dielectric losses, tan δ in the order of 10−2–10−1, respectively. Both the ɛ’ and tan δ values of the BMSN pyrochlores showed a nearly two-fold decrease with increasing Sr concentration. Negative temperature coefficient of capacitances, TCC, −408 to −713 ppm/°C were recorded over ~30–300 °C at 1 MHz.